STRESS RELATED FACTORS IN CAREGIVERS OF CHILDREN WITH AUTISM: OVER-LOAD, PSYCHOPATHOLOGY AND HEALTH - Seguí, José David; Ortiz-Tallo, Margarita; De Diego, Yolanda (Anales de Psicología / Annals of Psychology, 2008)
The objective of this study was to evaluate if caregivers were overloaded when their children were diagnosed with autism disorder, how it may influence their mental and physical health. 40 caregivers have been participating in this study, mainly mothers. The parameters studied include sociodemographic factors, caregivers burden overload (Zarit Scale, adapted to the Spanish language), Psychopathology (SCL-90) and health status (SF-60).The results indicate that caregivers were overloaded, and in a worse state of mental and physical health compared to the general population. A strong positive correlation was observed between overwhelmed carers and the evaluated health and pathopsicological parameters. These results are in accordance with previous findings that were published by other groups, supporting the idea that specific health programs are needed for caregivers of children with chronic diseases.